2017
DOI: 10.1136/jnnp-2017-317192
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune nodo-paranodopathies of peripheral nerve: the concept is gaining ground

Abstract: Peripheral neuropathies are classified as primarily demyelinating or axonal. Microstructural alterations of the nodal region are the key to understand the pathophysiology of neuropathies with antibodies to gangliosides and the new category of nodo-paranodopathy has been proposed to better characterise these disorders and overcome some inadequacies of the dichotomous classification. Recently, the research in autoimmune neuropathies has been boosted by reports of patients carrying immunoglobulin G4 antibodies ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 77 publications
3
64
0
2
Order By: Relevance
“…Analysis of myelinated fibers in the skin biopsy of patients with anti-Nfasc155, CNTN1, or Caspr1 IgG4 antibodies showed morphological changes of the nodes of Ranvier, including elongation of the node and loss of neurofascin and Caspr1 staining at paranodes, which were absent or less prominent in seronegative CIDP cases or in the case with anti-Nfasc155 antibodies of an undetectable isotype. These data add to other recent histopathologic and neurophysiologic observations in patients with antibodies to nodal/paranodal proteins 14,25 and indicate that isotype determination appears to be crucial to correctly identify such patients and to guide treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Analysis of myelinated fibers in the skin biopsy of patients with anti-Nfasc155, CNTN1, or Caspr1 IgG4 antibodies showed morphological changes of the nodes of Ranvier, including elongation of the node and loss of neurofascin and Caspr1 staining at paranodes, which were absent or less prominent in seronegative CIDP cases or in the case with anti-Nfasc155 antibodies of an undetectable isotype. These data add to other recent histopathologic and neurophysiologic observations in patients with antibodies to nodal/paranodal proteins 14,25 and indicate that isotype determination appears to be crucial to correctly identify such patients and to guide treatment.…”
Section: Discussionsupporting
confidence: 70%
“…In keeping with this view, sural nerve biopsies from CIDP patients with anti-Nfasc155 IgG4 revealed specific alterations at paranodal regions with a loss of septate-like junctions (23)(24)(25), but did not show evidence of macrophage-mediated demyelination. The pathogenic mechanisms responsible for conduction slowing in patients with anti-Nfasc155 IgG4 thus appear different from those implicated in other CIDP patients, and further support the existence of nodo-paranodopathy (41). It is possible that paranodal demyelination, as observed in sural nerve biopsies (24,25), may also participate in conduction slowing or loss in patients with anti-Nfasc155 IgG4.…”
Section: Discussionmentioning
confidence: 82%
“…The destruction of axo-glial interactions around nodal and paranodal regions alters the normal distribution of voltage-gated sodium and potassium channels, which are essential for the generation of action potentials in the nodes of Ranvier, leading to abnormal conduction of the electrical impulse (Arroyo, Sirkowski, Chitale, & Scherer, 2004;Doppler et al, 2015;Hafer-Macko et al, 1996;Pollard & Armati, 2011;Salzer et al, 2008). One of the main mechanisms that leads to paranodal demyelination is mediated by autoantibodies (Dalakas, 2011;Devaux, 2012;Querol, Devaux, Rojas-Garcia, & Illa, 2017;Uncini & Vallat, 2017). Indeed several recent studies have revealed the presence of autoantibodies against paranodal proteins such as neurofascin-155…”
Section: Demyelinating Schwann Cells In Inflammatory Segmental Demymentioning
confidence: 99%